Language Is not Enough - Knowledge Perspectives on Work-Based Learning in Global Organisations - Dohn, Nina Bonderup; Kjær, Christopher (HERMES - Journal of Language and Communication in Business, 2009)
In many larger organisations, increased globalisation has made more acute the need for a continuing competence development of employees, collaborators and customers. For logistic and ﬁnancial reasons, companies such as Danfoss A/S and Danske Bank have chosen to deliver many of their competence development courses in a purely virtual setting, utilizing various synchronous and asynchronous ICT-tools. The aim of this article is to present a view of competence as ‘knowledge in practice’ and explore the pedagogical implications of this view for such ICT-based competence development. The ‘knowledge in practice’ of the competent employee, it is argued, is a unity of linguistically expressible and tacit (experiential and practical) aspects. The article discusses how competence development courses can be designed as work-based blended learning in order to at once support practitioners in invoking the tacit dimensions of their knowledge and in innovating the practices from which these tacit dimensions stem. A concrete example of a course design which meets these requirements is presented. The example concerns a case study conducted by C. Kjær at Danfoss in its global educational unit Danfoss Refrigeration & Air Condition Academy (Danfoss RA Web Academy).